CHARACTERIZATION OF ACTIVE LANDFILL LEACHATE AND ASSOCIATED IMPACTS ON EDIBLE FISH (ORECHROMIS MOSSAMBICUS) - C.U, Emenike; S.H, Fauziah; P., Agamuthu (Malaysian Journal of Science, 2011)
Fish is an organism of both ecological and economic importance. Its existence in the water helps to sustain aquatic ecosystem via energy transfer. However, pollution can serve as a deterrent to its survival. Leachate from landfills and open dumps are generated due to waste deposition and associated water percolation which finds its way into water courses or even aquifer. Therefore this study was designed to characterize raw leachate from an active landfill and subsequently assess its potential impacts on edible fish, Orechromis mossambicus. The physico-chemical analysis of the leachate showed almost a neutral acid-base ratio (pH 7.35±0.6), with corresponding 27,000 and 51,200 mg/L for BOD5 and COD, respectively. Low ammonium content was recorded (0.09 mg/L) while the concentrations of some metals namely Zn (828 mg/L), Cr (25 mg/L), Ni (19.5 mg/L) exceeded allowable effluent discharge limits according to the Malaysia EQA 1974 Standards. The deep black colouration of the raw leachate was associated with high concentration of total dissolved solids (1,730 mg/L). Five different concentrations of the leachate (2.5 – 3.8% v/v) based on the range finding test, were applied definitively to obtain the effluent’s lethal concentration (LC50) on the named fish. Acute toxicity test of the raw leachate on O.mossambicus via static method revealed an LC50 of 3.2% v/v as calculated using Finney’s probit analysis from EPA. Mortality rate of the fish increased with increase in leachate concentration. It shows that the presence of some of the aforementioned components like BOD5, COD and even the metals in the leachate is not ideal since that reflects potential toxic compounds. The fish mortality observed in the research can be attributed to the physico-chemical constituents of the landfill leachate. This study concludes that based on characterization, leachate generated from landfills contain potentially toxic components. These constituents of leachate made it very dangerous for edible fish like O.mossambicus as it caused its mortality.